Farm size and effects of chemical fertilizer price on farm households: Insights from Nepal Terai - Takeshima, Hiroyuki; Shivakoti, Sabnam; Bhattarai, Binod; Karkee, Madhab; Pokhrel, Suroj; Kumar, Anjani (International Food Policy Research Institute, 2016)
This research explores how inputs such as chemical fertilizer that are often complementary to labor can benefit smallholders in countries like Nepal. These and other inputs complement labor when a country experiences periods of increased labor scarcity due to rising wages in rural areas. The future of smallholders in Asian countries is vigorously debated in the policy and research arena. An increasing number of studies indicate that in the face of rising rural farm wages, growing mechanization is gradually shifting the advantages enjoyed by smallholders to slightly larger farms in many Asian countries, including Nepal. While the evidence is limited, earlier studies suggest that this trend may also be associated with a greater return to the use of chemical fertilizers by larger farms than by their smaller counterparts. In this paper, we further assess the relationship between the role of chemical fertilizer and farm size in lowland Nepal. In particular, we assess the different effects of chemical fertilizer price on large versus small farm households, depending on farm size. We use the 2003 and 2010 panel data from the Nepal Living Standard Survey. Results generally suggest that in Nepal Terai, lower chemical fertilizer price seems to increase the per capita incomes of farm households with larger landholdings more than it does those with smaller landholdings. The mechanism is somewhat complicated; typically, larger farms benefit through an increased supply of crops from sharecropped/rented farms, which leads to a potential increase in forage supply and increased revenues from livestock production. However, greater benefits for larger farms through this mechanism remains consistent with the greater return to chemical fertilizer among larger farms. This is contrary to the notion that chemical fertilizer is a land-saving input that benefits smaller farms relatively more than it does larger farms. We conclude that fertilizer policy in Nepal should be designed within the broader framework of longer-term agricultural-sector strategies that will impact the future of smallholder farmers.